Analisis Peningkatan Kinerja Karyawan Di UP PTSP Kecamatan Makasar dengan Metode Structural Equation Modelling (SEM) - Arif Rahman; Surya Perdana (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
The decline in employee performance at UP PTSP Makasar District is characterized by a decreased level of service time efficiency in the area of KRK and IMB licensing. In addition, the cause of the decline in employee performance is due to the behavior of employees who like to postpone work and come late to work intentionally, and also employees lack the determination of high morale at work. The achievement of the duties of UP PTSP employees in Makasar Sub-District was not in accordance with the determined time standard. The purpose of this study was to determine the effect of the work environment and workload on the performance of UP PTSP Makasar District employees and to know the factors that had to be prioritized to become better. The data used for research is questionnaire data which is processed by the Structural Equation Modeling (SEM) method. This study analyzes the factors of work environment and workload using Structural Equation Modeling (SEM) with AMOS applications. Based on SEM output regression weights value states that there is no significant effect between work environment on employee performance. While there is a significant effect between workload on employee performance. The main priority in improving employee performance through the work environment is cleanliness in the workplace. The main priority in improving employee performance through better workloads is with work conditions at the workplace.